Flexible film vest formula solar charging ware - XIA MINGGUANG; XIA YING; ZHAO LIANG (2017)
The utility model discloses a flexible film vest formula solar charging ware relates to solar energy technical field, including vest undershirt, film battery module, terminal box, film battery module locates on the vest undershirt and is connected with the terminal box, film battery module includes the same film battery module of structure no. 1 and film battery module no. 2, film battery module's no. 1 positive output end and film battery module's no. 2 cathode output is connected, film battery module's cathode output and film battery module's no. 2 positive output hold be connected to respectively the terminal box correspond positive and negative terminal on, the utility model discloses can combine with the health clothing, satisfy the demand that long -term outdoor operations intelligence product charges, simple structure, the practicality is strong. 本实用新型公开了种柔性薄膜马甲式太阳能充电器，涉及太阳能技术领域，包括马甲背心、薄膜电池模块、接线盒，所述薄膜电池模块设于马甲背心上并与接线盒连接，所述薄膜电池模块包括结构相同的薄膜电池模块和薄膜电池模块二，所述薄膜电池模块的正极输出端与薄膜电池模块二的负极输出端连接，薄膜电池模块的负极输出端与薄膜电池模块二的正极